An analysis of land and property development models, and stakeholders: A case of National Capital Region, India. (June 2022) - Gupta, Ashish; Tiwari, Piyush
Abstract: With urbanization, successful land development has become critical for the growth of the cities. Land administration plays an important role in the outcome of land and property development models. Land and property development requires close coordination between public and private sectors and has impact on various stakeholders including public authority, private developers, landowners, home-buyers and society. In addition to land development, which has it's characteristic and price mechanism separate from property development, this paper looks at property development to provide a holistic approach to urban development. We examine three cases of land and property development models across different cities within a single regional planning area called the National Capital Region (NCR) in India. Firstly, we look at the National Capital Territory of Delhi (Delhi) that has for years adopted public sector model of land development, however, with limited success. Delhi has recently experimented with land pooling to unlock large peri-urban areas in the fringe. Secondly, Gurugram (Haryana) hailed as 'Millennium City' has been able to achieve high decadal real estate growth with Public-Private land development, but there is a cost to this fast growth to the society that results in severe planning and infrastructure bottlenecks. Lastly, we look at the Public land development model of Noida (Uttar Pradesh), which is distinct from Delhi and Gurugram, and has been able to provide one of the best infrastructures in NCR. But due to its pro-developer land allotment policy, it has created a city with several stalled projects that have resulted in the loss of home equity for home-buyers. These contrasting land development models when studied with property development models within the same geographical region provide key insights for policymakers, planners, city governments and academic fraternity. Highlights: Land development has an impact on stakeholders - public authority, private developers, landowners, home-buyers and society. In addition to land development, this paper looks at property development to provide a holistic approach to urban development. Land development models studied in NCR are public (in Noida), public-private (in Gurugram) and land pooling (in Delhi). Findings provide key insights for policymakers, planners, city governments and the academic fraternity.